Financial Sector Assessment Program : Review, Lessons, and Issues Going Forward. (Policy Papers; Policy Paper ;, 2005)
This paper reports on developments in the Financial Sector Assessment Program (FSAP) since the last Board review of the FSAP in spring 2003 and discusses staff views of the programs evolution.